Kosovo : Economic and Social Reforms for Peace and Reconciliation - World Bank (Washington, DC, 2013)
The report discusses the principal economic, and social reform policy tasks, Kosovo is facing, following the decade-long losses due to civic exclusion of a major part of its ethnic population, the absence of investments, and the neglect of physical, and human capital, a period which culminated in the 1999 conflict. It intends to inform on the framework of the United Nations Interim Administration in Kosovo, i.e., the consolidation of peace, by fostering social reconciliation, towards achieving sustainable economic growth in the province. The key challenges to the political economy address: 1) the formulation of a sustainable budget, increasingly financed through local taxation, hence, with reduced reliance on external donor support. Fiscal institutions need to be developed to ensure efficient public spending; 2) the establishment of trade liberalization, and a customs regime, to increase the potential for growth, and exports, allowing as well to benefit from the arrangements fostered by the Stability Pact, and the European Union; 3) the use of hard currency for internal transactions, and savings, and, the development of a strategy for banking sector development; and, 4) the creation of a reformed framework to encourage growth, by stimulating private enterprise development. Moreover, three aspects of social policy call for: an education policy at par with competitor countries; health policy that strengthens health care delivery, and addresses the effects of recent social traumas; and, social protection regarding a highly vulnerable population.